Chapter 9 Expanded Interiors Bringing contemporary site- specific fine- art practice to Roman houses at Herculaneum and Pompeii - Huber, Catrin (Taylor & Francis, 2020)
"Contemporary Art in Heritage Spaces considers the challenges that accompany an assessment of the role of contemporary art in heritage contexts, whilst also examining ways to measure and articulate the impact and value of these intersections in the future. Presenting a variety of perspectives from a broad range of creative and cultural industries, this book examines case studies from the past decade where contemporary art has been sited within heritage spaces. Exploring the impact of these instances of intersection, and the thinking behind such moments of confluence, it provides an insight into a breadth of experiences - from curator, producer, and practitioner to visitor - of exhibitions where this juncture between contemporary art and heritage plays a crucial and critical role. Themes covered in the book include interpretation, soliciting and measuring audience responses, tourism and the visitor economy, regeneration agendas, heritage research, marginalised histories, and the legacy of exhibitions. Contemporary Art in Heritage Spaces will be essential reading for academics and students engaged in the study of museum and heritage studies and contemporary art around the globe. Museum practitioners and artists should also find much to interest them within the pages of this volume. "